A formação continuada de professores da educação infantil de Sorocaba (SP): uma análise a partir da obrigatoriedade implementada pela Lei 12.796/2013. - Pereira, Meira Chaves (Universidade Federal de São Carlos, 2017)
The objective of this study is to understand the perceptions of pre school teachers working in the city 's schools about how they perceive the ongoing formation process offered by the Education Department, after the implementation of Law 12.796 / 13 and the compulsory offer of Early Childhood Education From the age of four in the Municipal Education Network of Sorocaba (SP). Necessary or necessary referrals to the new demands of this level of education from semistructured questionnaires and interviews with teachers of the municipal teaching network. The procedural basis for the development of this research will include the bibliographical survey of the theme, the contextualization of the new organization of basic education in the national and municipal sphere through official documents. The theoretical basis was anchored in Rosemberg (2003), Kramer (2003), Real (2000). Empirical research will be oriented to the analysis of content based on Bardin (2009). We chose the quantitative and qualitative approach Minayo (1996), because it is an investigative approach, whose primary concern is to understand the phenomenon, to describe the object of study, to interpret its values and relations, not dissociating the thought from the reality of the social actors where researcher and researched are recurrent subjects, and as a consequence, active in the development of scientific research. This research may also contribute to the development of similar works in other regions of Brazil, due to its timeliness and relevant recurrence.
The continued education of teachers of children´s education on Sorocaba (SP): an anlysis form compulsory implemented by Law 12.796/2013
Keywords: Formação continuada de professores; Obrigatoriedade da educação infantil; Educação infantil em Sorocaba; Continuing teacher education; Compulsory education; Child education in Sorocaba; CIENCIAS HUMANAS::EDUCACAO